"Too big to fail"? The Agrokor case and its impact on West Balkan economies. Issue 1 (22nd March 2019) - Djuric, Djuro; Jovanovic, Vladimir
Abstract: From about April 2017, Agrokor became the main economic topic in the Balkans. Once the greatest pride of the Croatian economy, it became a serious problem for its government. Its systemic importance for the country and the region required an immediate legislative solution. The Government had Parliament pass a special law intended to save this company. The special law on the procedure of extraordinary administration in companies of systemic importance adopted in April 2017 is an interesting example, because it introduced a new insolvency procedure titled "extraordinary administration" clearly following the example of the Italian Legge Marzano, which was adopted in order to save the Parmalat group in 2003. It also represents an example of a collision of legislation in the case of cross‐border insolvency proceedings inside and outside of the European Union, where different jurisdictions have diverging standpoints on the question of its recognition as a foreign insolvency procedure. However, once the rescue proceedings began, numerous (and some dubious) interests of the different stakeholders came to the light. The government tried not only to rescue the company and its assets throughout the Balkans region but also to acquire control of it. This was especially visible through the prerogatives of the extraordinary commissioner, formally appointed by the court, but in fact a government official. Creditors at risk, mainly Russian and Italian banks, filed lawsuits to prevent the selling of the debtor's assets. At the end, the majority creditors called to vote on the settlement agreement became the new owners of the company. However, Agrokor is still far from the end of the crisis. It has more than 60, 000 employees in the region and their destiny depends on the outcome of the crisis. In more recent times, the case also revealed major political scandals.